PERBANDINGAN PENDAPATAN USAHATANI KELAPA SAYUR (Cocos nucifer L) DENGAN KELAPA KOPYOR DI KECAMATAN DUKUHSETI KABUPATEN PATI - Mukhlis Mu'alim; Ari Astuti (Fakultas Pertanian UST, 2018)
This research was conducted in Ngagel Village, Dukuhseti Subdistrict, Pati Regency. The purpose of this research is to know the comparison of income and the feasibility of kopyor coconut and vegetable coconut farm with the hypothesis is income and the level feasibility of coconut kopyor farm is higher than vegetable coconut farm. The method to determining the research area was with purposive sampling, while the sampling method using simple random sampling with the number of respondents is 60, 30 vegetable coconut farmers and 30 farmers of kopyor coconut. Analysis method for this research is the analysis of income and feasibility, and so testing hypothesis using t test. From the result of analysis, showed the income of vegetable coconut is Rp. 82.986.534/Ha and coconut kopyor is Rp. 151,957,700/Ha. The feasibility analysis shows the value of feasibility kopyor coconut is higer than vegetable coconut, with R/C Ratio 6.31 and B/C Ratio 5.31 for vegetable coconut, than R/C Ratio 4,84 and B/C Ratio 3,84 for kopyor coconut. Depending firts t test with Î± = 0,1, the value of t test is higer than t table its means the income of kopyor coconut farming higher than vegetable coconut. But the level of feasibility analysis with t test showed that feasibility of kopyor coconut is lower than vegetable coconut because t test is lower than t table.